2024
DOI: 10.3389/fphar.2024.1359618
|View full text |Cite
|
Sign up to set email alerts
|

Emerging antioxidant therapies in Friedreich’s ataxia

Fred Jonathan Edzeamey,
Zenouska Ramchunder,
Charareh Pourzand
et al.

Abstract: Friedreich’s ataxia (FRDA) is a rare childhood neurologic disorder, affecting 1 in 50,000 Caucasians. The disease is caused by the abnormal expansion of the GAA repeat sequence in intron 1 of the FXN gene, leading to the reduced expression of the mitochondrial protein frataxin. The disease is characterised by progressive neurodegeneration, hypertrophic cardiomyopathy, diabetes mellitus and musculoskeletal deformities. The reduced expression of frataxin has been suggested to result in the downregulation of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 156 publications
0
1
0
Order By: Relevance
“…As known, SOD and CAT are enzymatic antioxidants ( Demirci-Cekic et al, 2022 ). SOD converts O 2 − to H 2 O 2 , which is hydrolyzed by CAT to harmless molecules ( Edzeamey et al, 2024 ). Wang et al (2016) reported that CoCL 2 treatment of embryonic rat heart cell cultures for 24 h caused a decrease in antioxidant SOD and CAT activities.…”
Section: Discussionmentioning
confidence: 99%
“…As known, SOD and CAT are enzymatic antioxidants ( Demirci-Cekic et al, 2022 ). SOD converts O 2 − to H 2 O 2 , which is hydrolyzed by CAT to harmless molecules ( Edzeamey et al, 2024 ). Wang et al (2016) reported that CoCL 2 treatment of embryonic rat heart cell cultures for 24 h caused a decrease in antioxidant SOD and CAT activities.…”
Section: Discussionmentioning
confidence: 99%